ANALISIS KINERJA TIM PROYEK TERHADAP KEBERHASILAN PROYEK - Arifal Hidayat (Jurnal APTEK, 2013)
Project team is the one of the substance structures of construction industry to execute a project. Project team has had the unique characters. Project team’s structure organization is used in short time period of the project. Project team to consist of the men who have competent in their knowledge and work relationship. Effectively and efficiency of project teamwork are requirement of project’s success in the different environment. There are any factors would influence the performance of the project team. This research aims to identify influence factors of performance project team and to analyze correlation of those factors towards project’s succes. The instrument of this research was adopted from Bubshait and Farooq articles as to Team Building and Project Success. This study was explored by using quistionnaire through project managers, site managers, and project’s staff from contractors, consultants, and the owners in Pekanbaru, Pelalawan, and Pasir Pengaraian. The Coefficient of Concordance Kendall and the Pearson’s correlation are used to analyze this study.